Scurvy: still a threat in the well-fed first world?. Issue 4 (7th August 2018) - Ceglie, Giulia; Macchiarulo, Giulia; Marchili, Maria Rosaria; Marchesi, Alessandra; Rotondi Aufiero, Lelia; Di Camillo, Chiara; Villani, Alberto
Abstract : We report three cases of scurvy in previously healthy children referred to us for leg pain and refusal to walk. All children had no significant medical history, symptoms had started months before and subtly advanced. Two of them presented with gingival hyperplasia and petechiae, another one reported night sweats and gingival bleeding in the past few weeks. Two had vitamin D deficiency, and all had microcytic anaemia (in one case requiring transfusional support). A nutritional screening revealed low or undetectable levels of ascorbic acid. This, along with the clinical and radiological findings, led to a diagnosis of scurvy. Vitamin C supplementation was started with rapid improvement of the children's clinical condition. Scurvy is a rare disease in the 'first world', but there are anecdotal reports of scurvy in children without any of the known risk factors for this condition. In our cases, a selective diet was the only risk factor.